THE IMPLEMENTATIONS OF CLASSROOM MANAGEMENT BY NON-NATIVE ENGLISH SPEAKER TEACHER - Ramadani Desi Vitaloka; Desi Sri Astuti; M. Iqbal Ripo Putra; Dayat Dayat (IKIP PGRI Pontianak, 2023)
This study aims to execute the implementation of classroom management in English from non-native English speaking teachers at SMK Bina Bangsa Meliau. The subjects in this study were two English teachers at the school, where the two teachers taught English using different methods. Researchers used interviews and also observations in this study, interviews were conducted by the two research language teachers, and observations were made by involving the teacher and students in the class when the learning took place. This study uses qualitative data analysis techniques from Ary, et al. (2010: 481). From the results of interviews and observations, it can be seen that the problem-solving method used by the teacher has advantages and disadvantages based on circumstances and environmental situations and usage. The results of the observations prove the teacher's statement in the previous interview.